Influence of Café Atmosphere, Lifestyle, and Brand Image on Purchasing Decisions - Forever, Febiwenesya; Yutika, Fitri (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The phenomenon of the rapid proliferation of cafés today reflects that spending time at cafés has become a part of Generation Z’s lifestyle. Consequently, coffee shops are no longer just selling coffee products but are also offering an atmosphere or ambiance as part of the overall customer experience. This study examines and analyzes the influence of store atmosphere in cafés, lifestyle, and brand image on purchasing decisions through the mediating role of service quality among coffee shop visitors. The research employs a quantitative approach, with data collected through an online questionnaire distributed via Google Forms. The population of this study consists of Generation Z individuals aged 17 to 28 years who have previously dined in at a coffee shop. The sampling technique used is purposive sampling, resulting in a total of 110 respondents. Data analysis was conducted using the partial least squares structural equation modeling (PLS-SEM) approach with the assistance of SmartPLS 3.0. The results of this study indicate that store atmosphere in cafés has a positive and significant influence on service quality. This implies that the more comfortable the atmosphere of a café, the better the perceived quality of service. However, store atmosphere in cafés does not have a significant influence on purchasing decisions. Furthermore, service quality, as a mediating variable, does not have a significant effect on purchasing decisions. Therefore, it is recommended that future research consider additional or alternative mediating variables that were not examined in this study or focus more narrowly on a specific coffee shop that adheres to consistent service standards.